Less Rationality, More Efficiency: a Laboratory Experiment on "Lemon" Markets. - Annette Kirstein; Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2004)
We have experimentally tested a theory of bounded rational behavior in a "lemon market". It provides an explanation for the observation that real world players successfully conclude transactions when perfect rationality predicts a market collapse. We analyzed two different market designs : complete and partial market collapse. Our empirical observations deviate substantially from these theoretical predictions. In both markets, the participants traded more than theoretically predicted. Thus, the actual outcome is closer to efficiency than the theoretical prediction. Even after 20 repetitions of the first market constellation, the number of transactions did not drop to zero. Our bounded rationality approach to explain these observations starts with the insight that perfect rationality would require the players to perform an infinite number of iterative reasoning steps. Bounded rational players, however, carry out only a limited number of such iterations. We have determined the iteration type of the players independently from their market behavior. A significant correlation exists between iteration types and observed price offers.
Keywords: D8; C7; B4; 330; guessing games; beauty contests; market failure; adverse selection; lemon problem; regulatory failure; paternalistic regulation; Marktmechanismus; Asymmetrische Information; Adverse Selection; Beschränkte Rationalität; Spieltheorie; Experiment